2008
DOI: 10.1080/00036840600707100
|View full text |Cite
|
Sign up to set email alerts
|

The impact of newspapers on consumer confidence: does spin bias exist?

Abstract: It is sometimes argued that news reports in the media suffer from biased reporting. Mullainathan and Shleifer (2002, 2004) argue that there are two types of media bias. One bias, called ideology, reflects a news outlet's desire to affect reader opinions in a particular direction. The second bias, referred to as 'spin' or 'slanting', reflects the outlet's attempt to simply create a memorable story. Competition between outlets can eliminate the effect of ideological bias, but increases the incentive to spin or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 5 publications
1
41
0
2
Order By: Relevance
“…Also in political science and economics (e.g. Miller et al, 1979;Alsem et al, 2008;Campbell et al, 2003) consumer confidence and behaviour is found to be significantly affected by media publications, and also here, the effects are often found to last temporarily and to disappear in the longer run.…”
Section: Impact Of Media Communication In Other Research Fieldsmentioning
confidence: 99%
“…Also in political science and economics (e.g. Miller et al, 1979;Alsem et al, 2008;Campbell et al, 2003) consumer confidence and behaviour is found to be significantly affected by media publications, and also here, the effects are often found to last temporarily and to disappear in the longer run.…”
Section: Impact Of Media Communication In Other Research Fieldsmentioning
confidence: 99%
“…They find that unemployment rate, inflation rate, change in housing wealth, and lagged confidence are correlated with aggregate consumer confidence. Since then, other researchers have focused on other variables such as the real interest rate and public debt (de Mendonca, 2009), the stock market (Lopez and Durre, 2003;Golinelli and Parigi, 2003;Jos Jansen and Nahuis, 2003), and news coverage (Alsem et. al., 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…2 Suppose there is a large negative shock to the labor market (a large negative value of ε), say because of a new tax on corporations, which raises their costs and leads them to reduce their level of employment. Even if the value of σ is zero, in which case the herd-behavior effect is zero, corporations will reduce their level of employment.…”
Section: The Model With a Supply Shockmentioning
confidence: 99%
“…The signs of A and Δ are negative if the following condition holds: 2 . s i   (15) In the standard saving-investment diagram, taught in introductory macroeconomics courses, (15) is often imposed when illustrating the "paradox of thrift," so it can be called the "paradox-of-thrift condition."…”
Section: The Model With a Supply Shockmentioning
confidence: 99%
See 1 more Smart Citation